Management of SamiSade in Village Infrastructure Development in Bogor Regency - Wulandari, Sally; Sutrisno, Edy (KnE Social Sciences, 2025)
The One Billion One Village Program (SamiSade) in Bogor Regency is a crucial initiative aimed at accelerating village infrastructure development and reducing the developmental gap between rural and urban areas. While this program has improved the quality of life for rural communities, its implementation faces several significant challenges. The identified issues in SamiSade management include the inefficient use of funds, lack of oversight and transparency, and project delays. Funds are often misallocated and or experience overruns due to inadequate planning and poor coordination. Additionally, financial accountability processes frequently do not adhere to applicable accounting standards, leading to undetected fund misuse. This study analyzes the management of the SamiSade Program and formulates policy recommendations for its management. It contributes to the literature on managing village infrastructure and development programs and proposes relevant policies. This study was conducted through observation and in-depth interviews with relevant departments and agencies. It highlights the need for clear and firm regulations on SamiSade fund management to enhance transparency and accountability as well as close loopholes that allow fund misappropriation. Implementing such a policy is expected to improve the effectiveness and efficiency of SamiSade fund management, as well as the sustainability of village infrastructure. This will maximize the program’s benefits for all village residents while supporting national development.